Shranjevanje matičnih celic iz popkovnične krvi - danes in jutri - Rožman, Primož (Zdravniški vestnik, 2012)
Umbilical cord blood (UCB) is an abundant source of haematopoietic stem cells (HSC) for allogeneic HSC transplant. In addition to HSCs, the cord blood and placenta contain ample nonhaematopoietic stem cells, which increasingly raise the interest of regenerative medicine. Public UCB banks have more than 500.000UCB units in international UCB registries that are available for the international exchange. It is estimated that additional two-fold number of units are held in the private UCB banks that store the cells for autologous purposes. Although the development of hybrid UCB banks was predicted in which the private units of UCB could be used for allogeneic purposes if needed, thishas not yet happened. The activity of UCB registries is complementary to the bone marrow donor registries, which keep the data of more than 16 million donors. The key data for international exchange of UCB are the HLA typing results and the stem cell count in the UCB units. The majority of international associations and bodies do not support the autologous UCB banking based on the current poor evidence on the usefulness of autologous UCBcells. However, this opinion is changing owing to the development of regenerative medicine so changes of the ethical and expert opinions are expected. In Slovenia, the only public UCB bank is maintained at the Blood Transfusion Centre of Slovenia, whereas the only private UCB bank is Biobanka.Since unlimited expansion in the number of UCB units does not increase the like-lihood of finding HLA-identical grafts, in Slovenia we plan to collect maximum up to 2000 UCB units. In order to foster the solidarity andequal accessibility, one needs to assure the use of UCB derived cells for children and adults for their possible treatment in the future.
Keywords: Blood Banks; Blood Donors; Fetal Blood; Hematopoetska matična celica, presaditev; Hematopoietic Stem Cell Transplantation; Krvne banke; Krvodajalci; Matične celice; Plodova kri; Popkovnične arterije; Popkovnične vene; Registri; Registries; Stem Cells; Umbilical Arteries; Umbilical Veins